Economic impact of natural disasters' fatalities - Padli, Jaharudin; Habibullah, Muzafar Shah; Abdul Hamid, Baharom (Emerald Group Publishing, 2010)
Purpose: The purpose of this paper is to find the meaningful relationship between the economic impact of the natural disaster and economic condition. Design/methodology/approach: The paper employed cross-sectional analysis to investigate the relationship between economic condition namely, gross domestic product per capita (GDPpc); gross domestic product per capita squared (GDPpc2); government consumption ratio to GDP (gc); ratio of M2 over GDP(M2); years of schooling attainment (sc); land area and finally; population and the economic impact of natural disasters, whereby ten types of natural disasters were chosen. The degree to which the human and economic losses due to these ten natural disasters were measured by, the variables selected are, number of killed; total affected; and ratio of total damage to GDP. Three different points of time were regressed, namely, 1985, 1995, and 2005 covering 73 countries. Findings: Results clearly indicate that there seems to be meaningful relationship between the economic impact of natural disasters and economic conditions. Practical implications: The paper provides some evidence on the important role of economic condition in minimizing the impact of natural disasters. Originality/value: The paper incorporates a comprehensive list of explanatory variables in accounting for natural disaster fatalities.